2022
DOI: 10.1177/02537176221111578
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the AIIMS Facial Toolbox for Emotion Recognition

Abstract: Background: Emotional facial expression database, used in emotion regulation studies, is a special set of pictures with high social and biological relevance. We present the AIIMS Facial Toolbox for Emotion Recognition (AFTER) database. It consists of pictures of 15 adult professional artists displaying seven facial expressions—neutral, happiness, anger, sadness, disgust, fear, and surprise. Methods: This cross-sectional study enrolled 15 volunteer students from a professional drama college in India (six males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“… 34 However, just like Ekman, this category along with ‘others’, was eliminated due to low accuracy rates in phase I. Similarly, our findings from the previous study on emotion recognition of facial emotion in All India Institute of Medical Sciences (AIIMS) Facial Toolbox for Emotion Recognition (AFTER) database, 18 also found that the contempt emotion had poor hit rates among the study population. The same was also true for the Dynamic Emotion Laden Inventory of Videos for Emotion Recognition (DELIVER) database that assessed emotion recognition through videos of emotion expressions.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“… 34 However, just like Ekman, this category along with ‘others’, was eliminated due to low accuracy rates in phase I. Similarly, our findings from the previous study on emotion recognition of facial emotion in All India Institute of Medical Sciences (AIIMS) Facial Toolbox for Emotion Recognition (AFTER) database, 18 also found that the contempt emotion had poor hit rates among the study population. The same was also true for the Dynamic Emotion Laden Inventory of Videos for Emotion Recognition (DELIVER) database that assessed emotion recognition through videos of emotion expressions.…”
Section: Discussionsupporting
confidence: 60%
“…The data presented in the current article on the development of Emotion Laden Sentences Toolbox for Emotion Recognition (ELSTER) database is part of a larger study comprising the development of a larger toolbox for varying facets of emotion recognition. 18 , 32 This cross-sectional study was conducted from March 2019 to August 2021 at the Department of Psychiatry, All India Institute of Medical Sciences, New Delhi, India. The Institute Ethics Committee approved the study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations